Automotive system safety : critical considerations for engineering and effective management - Miller, Joseph (Joseph D.) (Hoboken, New Jersey : John Wiley & Sons, 2020)
"The book serves as a practical guide to incorporate system safety efficiently into an organization. The content is based on the author's experience and can aid small and large automotive companies, and the managers and engineers in those companies, to improve system safety. Further, it will be a useful tool for marketing, sales, and business development professionals to understand and converse knowledgeably with customers and prospects"--
Safety expectations for consumers, OEMs, and tier 1 suppliers -- Safety organization -- System safety vs. functional safety in automotive applications -- Safety audits and assessments -- Safety culture -- Safety lifecycle -- Determining risk in automotive applications -- Risk reduction for automotive applications -- Other discussion and disclaimer -- Summary and conclusions.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Automobiles -- Safety measures; Automobiles -- Safety appliances; Automobiles -- Design and construction; Electronic books